Motives and obstacles to political participation of working women (A field social study) - جواد كاظم, ناظم; احمد غريب, لقاء (Journal of College of Education, 2021)
The nature of the social and economic conditions that Iraq is going through have led to a weakening of the motives for the political participation of working women and have made women even educated, looking for education not as a way to qualify and work but rather to become a good wife and mother. Traditions prevent women from working in places and in certain roles, and traditions have led to determining the participation of women in leadership roles, and the position of working women is determined by their social role assigned to them and by civilization of society. Therefore, the motives for the political participation of working women are not limited to merely obtaining their political rights, but rather embodying respect for their social rights in the legitimacy of expressing their ideas freely within the framework of the institutions of society. The motives for political participation of working women have been linked to social and political factors that can be considered the most influential factors in participation Working women . Therefore, the political skills of working women must be expanded by improving educational opportunities and leadership courses and removing psychological, social, economic and political obstacles that limit the motives for political participation of working women.